Envases biodegradables a base de residuos de arroz como alternativa para reducir la contaminación por plásticos - Zambrano Mas , Escólin Dolores (2024)
The objective of this research is to evaluate the viability of biodegradable packaging made from rice residues (Oryza sativa L.), in order to reduce plastic pollution. The methodology used included a quantitative experimental design in which three treatments were tested, varying the proportions of starch, rice residues and glycerin (T1: 20%, 60%, 20%; T2: 30%, 50%, 20%; and T3: 40%, 40%, 20%). Three repetitions of each treatment were carried out, evaluating the effectiveness in moisture retention and other properties of the packaging produced under laboratory conditions. The results indicate that there were no statistically significant differences between the treatments (p > 0.05), suggesting that the variation in the proportions of the ingredients does not significantly affect the properties of the packaging. However, it was observed that the T3-R2 treatment achieved the lowest final humidity (8.50%), standing out in humidity reduction efficiency. This suggests greater material stability, a crucial aspect for the durability of biodegradable packaging